Experimental study of diode pump Nd-YAG laser - Iqbal, Syed Javaid; Khan, Nasrullah (2002)
We have studied the lasing characteristics of the Nd-YAG at different input waves, plane and concave mirrors and different percentage of reflecting mirrors. A conversion efficiency of 62.5% with a threshold at 94mW, CW 1064nm radiation was achieved with 805nm input. Similarly a conversion efficiency of 70% with threshold at 106mW was achieved. We have also studied the conversion efficiency of Nd-YAG It is found that plano-concave cavity for NdYAG laser is more efficient as. compared to, the plano-plane cavity. It is also found that the mirror with 95% high reflecting at 1064nm have the highest conversion efficiency but It also have higher threshold as compared to 99% high reflecting which has the lowest threshold which is about 47mW.